PELAKSANAAN PROGRAM INSEMINASI BUATAN BAYI TABUNG MENURUT HUKUM ISLAM DAN HUKUM POSITIF INDONESIA - Fuadi Isnawan (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2019)
This paper aims to examine the In Vitro Fertilization (IVF) program in the perspective of Islamic Law, and positive law in Indonesia, so that it is clear whether or not IVF practice is religiously or legally Indonesian. In conducting the analysis, the authors used a qualitative type of library research with a normative approach. The results of this paper are: (1) IVF artificial insemination program is allowed in Islamic Law, with the condition that the sperm must be from the husband himself. In vitro insemination with the uterine rental model Surrogate Mother, there are two opinions. The first opinion states that the Surrogate Mother is prohibited because it creates a mixture of lineage which is also related to mahram and inheritance. The second opinion states that Surrogate Mother was allowed on emergency grounds. (2) The implementation of IVF in Indonesia is regulated in Law Number 36 of 2009 concerning health. The Law stipulates how the requirements and procedures must be fulfilled in order to participate in the program so that the babies made in the program do not violate the ethics in society and religion